Application of Ultrasound for Oil Separation and Recovery of Palm Oil. (15th December 2012) - Juliano, P.; Swiergon, P.; Mawson, R.; Knoerzer, K.; Augustin, M. A.
Abstract: This work investigated whether ultrasound treatment could improve the oil recovery from the extract obtained from pressed oil palm mesocarp. Oil recoverable after subjecting two process streams from palm oil milling operations to ultrasound were compared to that obtained from corresponding samples without ultrasound treatment. The process streams examined were (i) the ex‐screw press feed into the vertical clarification tank and (ii) the underflow sludge from the clarification tank. Oil recoverable was taken as the sum of decantable oil obtained after a gravity settling process at 85 °C for 1 h (skimmed oil) and oil released from the remaining colloidal dispersion after centrifugation at 1, 000 g (centrifuged oil). Oil recoverable was dependent on the ultrasound treatment applied, type of transducer used and the feed stream. Increased recoverable oil was obtained by applying low frequency ultrasound (20 kHz) to the ex‐screw press feed using a long rod radial sonotrode system but recoverable oil was decreased when a short single step cascade focused sonotrode system was used. High frequency ultrasound (400 + 1, 600 kHz) increased recoverable oil from both process streams. Applying sequential low and high frequency ultrasound increased recoverable oil from the ex‐screw press feed but decreased that from the underflow sludge. The use of high frequency ultrasound for improving oil recovery is a significant advance for palm oil milling operations.